Analisis Determinan Permintaan Konsumen pada Coffee Shop di Kota Pekanbaru - Mardiah Mardiah; Yanti Mayasari Ginting; Indri Yovita (CV. ALIM'SPUBLISHING, 2026)
This research examines the influence of Price, Income, Taste, Promotion, Location, and Product Quality on consumer demand at Coffee Shops in Pekanbaru City. The population consists of Coffee Shop customers in Pekanbaru City. A nonprobability sampling method with Accidental Sampling technique was applied, involving 100 respondents. Data were analyzed using SEM-PLS approach through SmartPLS 4.0 software. The findings reveal that Price, Promotion, and Product Quality significantly influence consumer demand. In contrast, Income, Taste, and Location do not show a significant effect. Among all variables, Product Quality emerges as the most dominant factor affecting consumer demand at Coffee Shops in Pekanbaru City. Therefore, coffee shop managers in Pekanbaru City need to improve taste consistency, menu variety, presentation, and product quality standards to maintain and increase consumer demand. This research is expected to provide business owners with a basis for formulating more appropriate, competitive, and sustainable customer satisfaction-oriented marketing strategies in the local market.